2020
DOI: 10.3389/fphar.2020.594042
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Gut Microbiome: Therapeutic Strategy for Rheumatoid Arthritis During Pregnancy and Lactation

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovial inflammation and bone destruction. Microbial infection is considered to be the most important inducement of RA. The pregnancy planning of women in childbearing age is seriously affected by the disease activity of RA. Gut microbiome, related to immunity and inflammatory response of the host. At present, emerging evidence suggested there are significant differences in the diversity and abundance of gut microbiome during pregnancy and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 153 publications
0
6
0
Order By: Relevance
“…Studies indicated that the reconstitution of VLDLR expression in macrophages of VLDLR-deficient mice promotes the occurrence and development of atherosclerosis, which may be due to the accumulation of atherosclerotic lipoproteins caused by the knockout of VLDLR (124,125). The physical state of the mother has a profound impact on the health of the fetus (126,127). Maternal-fetal interface studies suggest that VLDLR can induce osteoclasts differentiation and inhibit the inflammatory response of macrophages (128)(129)(130).…”
Section: Maternal Vldlrmentioning
confidence: 99%
“…Studies indicated that the reconstitution of VLDLR expression in macrophages of VLDLR-deficient mice promotes the occurrence and development of atherosclerosis, which may be due to the accumulation of atherosclerotic lipoproteins caused by the knockout of VLDLR (124,125). The physical state of the mother has a profound impact on the health of the fetus (126,127). Maternal-fetal interface studies suggest that VLDLR can induce osteoclasts differentiation and inhibit the inflammatory response of macrophages (128)(129)(130).…”
Section: Maternal Vldlrmentioning
confidence: 99%
“…Specifically, changes in the oral and intestinal microbiota are associated with loss of tolerance to self-antigens and increased inflammatory events that promote joint damage (du Teil et al, 2019). Therefore, regulation of the oral or gut microbiota may be a strategy to treat or prevent the development of RA (Yao, Cai, Fei, Ren et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis is an immune-mediated chronic joint inflammation and injury featured by bone destruction and synovial hyperplasia [146]. In contrast, SCFAs, as modulators of the immune system [146], can alleviate arthritic symptoms and are emerging as a novel treatment strategy for RA.…”
Section: Scfas and Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Rheumatoid arthritis is an immune-mediated chronic joint inflammation and injury featured by bone destruction and synovial hyperplasia [146]. In contrast, SCFAs, as modulators of the immune system [146], can alleviate arthritic symptoms and are emerging as a novel treatment strategy for RA. gen-induced arthritis (CIA) model, found significantly higher SCFAs levels in the stool of mice after treated with SCFAs and reduced inflammatory cell infiltration and synovial hyperplasia in the knee and ankle joint cavities of mice [147].…”
Section: Scfas and Rheumatoid Arthritis (Ra)mentioning
confidence: 99%